(untitled) (Вісник: Міжнародні відносини, 2025)
The article examines scientific approaches to the study of global climate change and policies to counter it, based on theories of international relations, globalization, ecological modernization, sustainable development and climate justice. The communicative dimension of climate policy (ecological, risk, scientific, political and disaster communications) and their role in shaping the climate-motivated behavior of international actors are shown. The spectrum of scientific discussions on the causes of climate change is outlined – from anthropogenic warming to natural cycles - and the associated epistemic uncertainties for mitigation and adaptation strategies. The author’s concept of "climate humanism" is proposed, which combines countering climate change with the values of human rights, social justice and international responsibility. A theoretical and methodological basis for analyzing the climate policy of leading international actors in the context of modern global transformations is formulated.